Malignant pheochromocytoma with negative biochemical markers: Is it time to reclassify pheochromocytomas? - Borzouei, Shiva (Urol Case Rep, 2019)
Pheochromocytomas are catecholamine producing tumors of adrenal gland generally diagnosed by presence of these markers in urine or plasma. However, a few may be marker-negative and challenging for clinicians. Several reports of these marker-negative pheochromocytomas may warrant necessity for a new classification of these tumors. Adrenergic blockade before surgery is one of the main reasons for recognition of these cases. We present a case of marker-negative pheochromocytoma which turned out to be malignant on its recurrence. To our knowledge, this is the only case of malignant marker-negative pheochromocytoma reported in literature so far.